Slightly acidic electrolyzed water as a novel thawing media combined with ultrasound for improving thawed mutton quality, nutrients and microstructure - Dewei Kong; Rongwei Han; Mengdi Yuan; Qian Xi; Qijing Du; Peng Li; Yongxin Yang; S.M.E. Rahman; Jun Wang (Food Chemistry: X, 2023)
The effects of ultrasound-assisted slightly acidic electrolyzed water thawing (UET), air thawing (AT), water thawing (WT) and microwave thawing (MT) on the quality, nutrients and microstructure were investigated. The UET treatment did not affect the lightness (L*) but reduced the redness (a*) and yellowness (b*) of the mutton. The UET treatment could better maintain the textural properties. The UET group had a higher immobilized water and lower free water, which was closer to the state of the control group. The UET treatment not only effectively inhibited the lipid oxidation but also reduced the loss of nutrients, especially minerals. The microstructure of the UET group was smoother and more complete, and the muscle fibers did not show significant breakage. In conclusion, UET treatment could better maintain the quality, nutrients and microstructure of thawed mutton. Therefore, UET could be regarded as a potential thawing method for application in the processing of meat products.